"Tikkun Atzmi" (Healing the Self) or "Tikkun Olam" (Healing the World) – Motivation for Teaching in Special Education - Lavian, Rivka Hillel (Advances in Social Sciences Research Journal, 2014)
A large body of educational research has discussed the issue of motivation in choosing to become a teacher in mainstream education (Katzin & Shkedi, 2011; Perry & Friedman, 2011), whereas motivation for special education has only been researched in the last decade. Analysis of special education teachers’ life-stories in my PhD research (Hillel-Lavian, 2003) found that individual or family differences constituted major motives for majoring in special education. A follow-up research I conducted (Hillel-Lavian, 2013) sought to re-examine this issue through a wide overview of special education student-teachers. The research sought to examine, through life-stories, what motivated teaching students to select special education. The research group included 20 special education students in their last year of studies. The narratives yielded a picture of teachers imbued with motivation, the majority holding a rather personal approach to special education, due to individual and family differences; some were with learning disability, some were new immigrants, some sisters to siblings with special needs. In this article, I will relate to the findings of my research (Hillel-Lavian, 2003, 2013) while using two organizing metaphors: "Tikkun Atzmi" (healing the self) and "Tikkun Olam" (healing the world). Some of the student teachers came to teaching out of a desire for a corrective experience for themselves after a sense of failure in the mainstream education system, and others came with the intent to change the system, to make it better and more empathetic. This article is not just about special education teachers; it involves thinking about teaching differently. Metaphors can be a way to unlock the ontology and epistemology of teachers’ knowledge. Using the novel metaphors of "Tikkun Atzmi" (healing the self) and "Tikkun Olam" (healing the world), this article invites educators all over the world to participate in a discourse with many voices. And think differently.